Prediction of meat quality in Bali cattle using ultrasound imaging - Jakaria, J.; Khasanah, H.; Priyanto, R.; Baihaqi, M.; Ulum, M. F. (Diponegoro University, 2017)
The objective of this study were to predict carcass quality characteristics in Bali cattle using ultrasound imagery. The Number of samples were 81 heads of Bali cattle consist of bulls (62 heads) and cows (19 heads) with various age ranging from 1 to 6 years were collected their body weight and carcass qualities including backfat thickness (BF), longissmus dorsi thickness (LD), rump fat thickness (RF), rump thickness (RT), marbling score (MS) and the percentage of intramuscular fat (PIF). Those were estimated using ultrasound performed on 4.5-6,5 MHz frequency with depth of 8.8-13 cm. The BF, LD, MS and PIF measurement were applied on 12th-13th ribs, while the RT and RF measurement were conducted between ischium and illium. MS determination was calculated using Aus-Meat standard, while PIF was analysis based on Deaton and Rouse (2000). Body weight and carcass quality among traits were analyzed using descriptive and correlation procedures. The results showed that performance of body weight and carcass quality differs between Bali bulls and Bali cows, as well as among the age variations. Correlation analyses among traits (body weight and carcass quality) showed strong positive correlation (P<0.05) ranging from 0.291 to 0.938. In conclusion, ultrasound imaging method could be used to estimate carcass quality characteristics in Bali cattle.